CLINICAL STUDY OF JAMU FORMULA FOR GENU OSTEOARTHRITIS - Danang Ardiyanto; Sunu Pamadyo T. Ismoyo (Widyariset, 2013)
The uses of conventional drug for osteoarthritis treatment has been shown to give serious side effects. The use of jamu as a natural product for treatment of osteoarthritis needs a scientific evidence especially efficacy and safety evidence. This research is a quasi experiment pre post test design study that was conducted at Klinik Saintifikasi Jamu B2P2TOOT from March until December 2011. The giving of jamu formula that which consisted of 15 gram temulawak rhizome (Curcuma xanthorrhiza), 7 gram meniran herb (Phylanthus niruri), 15 gram kunyit rhizome (Curcuma domestica), 5 gram adas seed (Foeniculum vulgare), 5 gram rumput bolong herb (Equisetum debile), and 5 gram kumis kucing leaves (Orthosiphon stamineus) for2 months could improve clinical symptoms such as joint paint, swollen joints, movement disorders and tingling. Objectively the jamu formula decresed the joint paint with measurements of visual analogue scale. This formula in terms of safety did not interfere with liver and kidney function.